Diversity of the Native and Endemic Species of Tarai Region in Kumaun, Uttarakhand - Mathur, Anjali; Joshi, Hema (Indian Forester, 2014)
The present study is an attempt to explore the native and endemic plant species of tarai region of Kumaun Himalaya of Uttarakhand. The study site includes tarai area around Lalkuan in district Nainital and Pantnagar and Kichha tehsil in district Udhamsingh Nagar. The region is also characterized now with settlements of human beings of different culture from different places. During the study period it was found that the percentage of native species was 19.11 and endemic 2.09. Representation of 78.80% of non native species and very low percentage of native and endemic plant species in the study area indicated the high degree of disturbance due to anthropogenic pressure.